A COMPARATIVE ANALYSIS ON THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND SERVICE QUALITY IN PUBLIC AND PRIVATE UNIVERSITIES IN KENYA - Ngugi, Diana Wanjiku; Gachunga, Hazel; Mukanzi, Clive (Human Resource and Leadership Journal, 2021)
Purpose: The purpose of this study was to compare the relationship between Organizational Culture and Service Quality between public and private universities in Kenya. Methodology: The methodology of this study comprised of descriptive and causal research designs. The target population was 2,475 teaching staff in the 23 chartered public and 17 chartered private universities in Kenya. Sample size comprised of 225 teaching staff in the business program in two chartered public and two chartered private universities in Kenya. The collected questionnaires were 189 (Public 75, Private 114) which resulted in a response rate of 84%. Findings: The study findings showed that, in universities in Kenya, there was a significant difference in means of Organizational Culture between public (mean=3.60, p-value=0.000<0.05) and private (mean=4.13, p-value=0.000<0.05), with private universities having a higher mean. The study findings showed that, in universities in Kenya, there was a significant difference in means of Service Quality between public (mean=3.68, p-value=0.000<0.05) and private (mean=4.18, p-value=0.000<0.05), with private universities having a higher mean. The findings also showed that Organizational Culture has a positive, significant relationship with Service Quality in both public (r=0.649, p-value=0.000<0.05) and private (r=0.587, p-value=0.000<0.05) universities, where the relationship was stronger in public universities compared to private universities. Organizational Culture has a significant influence on Service Quality in Public universities (r2=0.421) and in Private universities (r2=0.345). The study concluded that there is indeed a significant, positive relationship between Organizational Culture and Service Quality in both public and private universities in Kenya. The Study also concluded that Organizational Culture was a significant predictor of Service Quality in both public and private universities in Kenya. Unique contribution to theory, practice and policy: This study made an outstanding contribution to theory by validating use of systems theory of management. The study also contributed greatly to theory by showing a significant relationship between Organizational Culture (using DOCS) and Service Quality (using SERVQUAL) as measurement instruments in public and private universities in Kenya. This study recommended that leadership in public universities needs to emulate the culture in private universities so that there is higher service Quality for the students. Also, leadership in private universities need to improve on how they use their strong and positive organizational culture to deliver Service quality to its students amidst the unique challenges they face.